Pengembangan Konsep Sistem Tata Surya di Tingkat Sekolah Dasar - Saputra, Hengki; Khasanah, Farinda Nur; Apriana, Wahyuni Isna; Kurniawati, Wahyu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the solar system there are two groups, namely the outer planet group and the inner planet group. The outer planet group is the planet that is far from the sun, while the inner planet group is the planet that is close to the sun. Apart from the two groups in the solar system there are also planets, including: Saturn, Mercury, Venus, Mars, Earth, Jupiter, Neptune and Uranus. The method used is descriptive analysis, the researchers describe in detail the Solar System. This method explains in detail about the solar system, the structure of the solar system, parts of the solar system and other objects in the solar system sourced from journals, the article then takes observations from the literature and ends with a conclusion from this literature analysis.